Syn‐Contractional Overprinting Between Extension and Shortening Along the Montagna Dei Fiori Fault During Plio‐Pleistocene Antiformal Stacking at the Central Apennines Thrust Wedge Toe. Issue 10 (16th October 2018) - Storti, F.; Balsamo, F.; Mozafari, M.; Koopman, A.; Swennen, R.; Taberner, C.
Abstract: The Montagna dei Fiori fault vertically offsets the crest of the NW‐SE trending Montagna dei Fiori anticline in the distal foothills of the central Apennines. There are several interpretations to explain this extensional fault system in close proximity to the Apennine deformation front. A prefolding age of the Montagna dei Fiori fault prevails in models and ideas, based on evidence of Triassic to Early Jurassic rift‐related faults and on thickness and facies distribution of Miocene sediments. However, overprint relationships between extension and shortening are generally speculative and relative age constraints are loose. In this paper we provide an alternative interpretation based on new structural and geochemical data that does not support any preshortening scenarios. The outcrops show that (1) failure of the prerift to syn‐rift Jurassic platform carbonates is controlled by a pattern of N‐S and E‐W fault trends, (2) cessation of fault activity coincides with a breakup unconformity of Late Jurassic age, and (3) a large variety of S‐C shear fabrics occurs along the Montagna dei Fiori fault. Petrography, C‐O stable isotope, and microthermometric data of calcite veins provide constraints on the environmental conditions of deformation. Our multidisciplinary data set favors a partitioning of strain by the interaction of horizontal shortening and related uplift, and by gravitational reequilibration controlled by antiformal stacking underneath the Montagna dei Fiori anticline. Therefore, shortening and extensional strain fields are genetically connected, coeval, while nucleating from different levels in the mechanical stratigraphy. We discuss the implications of this model on the seismo‐tectonic framework of active faulting in the central Apennines of Italy. Key Points: The Montagna dei Fiori (MdF) Fault offsets the crest of the MdF Anticline in the distal foothills of the Central Apennines by over 900 m Our multi‐disciplinary dataset does not support any pre‐shortening interpretation scenarios for the origin of the Montagna dei Fiori Fault We provide a new model in which shortening and extension are genetically connected and geologically coeval